Global AVHRR-derived land climatology - Gutman, Garik (National Environmental Satellite, Data and Information Center, National Geophysical Data Center, 1997)
Collection of data from 1987-88 Pathfinder Program. Goal is to make currently archived satellite data widely available to study global climate change--NGDC home page.